2012
DOI: 10.1007/s00268-012-1597-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Surgery: Barriers, Solutions, and the Role of Evidence Synthesis

Abstract: Poorly or inadequately performed RCTs and meta-analyses can give rise to incorrect results and thus fail to inform clinical practice or revise policy. The above barriers can be overcome by providing academic leadership and good organizational support to ensure that adequate personnel, resources, and funding are allocated to the researcher. Training in research methodology and data interpretation can ensure that trials are conducted correctly and evidence is adequately synthesized and disseminated. The ultimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 51 publications
1
57
0
2
Order By: Relevance
“…Following the wide uptake of robotic surgery among the various surgical specialties and the concurrently increasing experience with endoscopic parathyroidectomy and robotic thyroidectomy, robotic parathyroidectomy was the next advance [18, 19]. This innovative technique representing the “fourth generation” in the evolution of parathyroid surgery was first described by Tolley et al [5] in 2011 and involved a “scarless-in-the-neck” approach through an anterior chest (infraclavicular) incision and 3 trocars in the ipsilateral axillary line.…”
Section: Robotic Parathyroidectomymentioning
confidence: 99%
“…Following the wide uptake of robotic surgery among the various surgical specialties and the concurrently increasing experience with endoscopic parathyroidectomy and robotic thyroidectomy, robotic parathyroidectomy was the next advance [18, 19]. This innovative technique representing the “fourth generation” in the evolution of parathyroid surgery was first described by Tolley et al [5] in 2011 and involved a “scarless-in-the-neck” approach through an anterior chest (infraclavicular) incision and 3 trocars in the ipsilateral axillary line.…”
Section: Robotic Parathyroidectomymentioning
confidence: 99%
“…The cost of purchasing the da Vinci® surgical robot is GBP 1.5 million. Added to this are maintenance averaging GBP 120,000 per annum and surgical consumables at approximately GBP 1,300 per case [14]. Higher costs are achieved by the monopoly status of Intuitive Surgical Inc. in the surgical robotics market.…”
Section: Cost-effectiveness and Valuementioning
confidence: 99%
“…In today’s practice, evidence-based surgery is paramount and as such, no discussion would be complete without presenting this [14]. …”
Section: The Evidence Basementioning
confidence: 99%
“…However, the recent introduction of pure endoscopic techniques and well-established efficacy of medical therapy should lead to a theoretical five arms of study (medical vs endoscopic vs open surgery vs laparoscopy vs robotics), although such studies are very hard to design and to conduct. 8 All the esophageal procedures for benign disease were codified with a robotic approach, including those for achalasia, reflux disease, and diverticula. 21 A very large retrospective study by Shaligram The authors concluded that the perioperative outcomes were superior in the LM and RM groups when compared with OM.…”
Section: Esophagusmentioning
confidence: 99%
“…8 Nevertheless, the progressive popularity of RS among urologists, gynecologists, and patients, mixed with some industrial pressure, has led to the worldwide diffusion of the robot in many hospitals. 9,10 Interestingly, the pioneers 11,12 of general and gastrointestinal RS reported many benefits and few complications of this technique in terms of intraoperative morbidity, return to normal activities and, mainly, feasibility of some of the most complex procedures that were previously precluded by pure laparoscopy without the robotic interface.…”
Section: Introductionmentioning
confidence: 99%